The Effects of Cognitive Behavioural Theraphy and Yoga on Stress - Rathakrishnan, Balan; Parasuraman, Balakrishnan; Satrya, Aryana; Abdullah, Muhammad Madi Bin; Muniapan, Balakrishnan (Faculty of Psychology, Universitas Surabaya, 2009)
This study compares a stress management program based on cognitive behavioural therapy principles with yoga-based stress management program. A study sample of 30 students, 15 male and 15 female from one of the local university in Sabah, was taken as subjects. The subjects were divided into 3 equal groups. The first group was given cognitive behavioural therapy, the second group was given yoga and the last group treated as control group. Trained group leaders were instructed the first and second groups, and 10 sessions were held with each group, over a period of 4 months. Psychological (self-rated stress, anger, exhaustion and quality of life) measurements were obtained before and after treatment with questionnaire. The results indicate that cognitive behaviour therapy is a promising stress management technique compared to yoga therapy and the control group. However, both interventions do not have any significant effects on quality of life. Makalah ini mengkaji perbandingan antara suatu program pengelolaan stres berlandaskan prinsip-prinsip terapi perilaku kognitif dengan suatu program untuk mengatasi stres yang menggunakan te- rapi yoga. Sampel berasal dari 30 mahasiswa suatu universitas di Sabah, yang terdiri atas 15 pria dan 15 wanita. Subjek dibagi menjadi tiga kelompok yang sama besarnya. Kelompok pertama menerima terapi perilaku kognitif, kelompok kedua menerima terapi yoga, sedangkan kelompok terakhir menjadi kelompok kontrol. Instruktur-terlatih memberikan terapi kepada kelompok pertama dan kedua dalam 10 sesi un- tuk setiap kelompok selama empat bulan. Pengukuran psikologis terhadap tingkat stres, kemarahan, ke- lelahan, dan kualitas hidup dilakukan sebelum dan sesudah perlakuan dengan memakai kuesioner. Hasil studi menunjukkan bahwa terapi perilaku kognitif merupakan teknik pengelolaan stres yang menjanjikan jika dibandingkan dengan terapi yoga dan kelompok kontrol yang tidak diberi perlakuan. Meskipun de- mikian, kedua intervensi tersebut tidak menunjukkan dampak yang signifikan terhadap kualitas hidup.